LightHouse: An Automatic Code Generator for Graph Algorithms on GPUs - Shashidhar, G.; Nasre, Rupesh (Languages and Compilers for Parallel Computing, 2017)
We propose LightHouse, a GPU code-generator for a graph language named Green-Marl for which a multicore CPU backend already exists. This allows a user to seamlessly generate both the multicore as well as the GPU backends from the same specification of a graph algorithm. This restriction of not modifying the language poses several challenges as we work with an existing abstract syntax tree of the language, which is not tailored to GPUs. LightHouse overcomes these challenges with various optimizations such as reducing the number of atomics and collapsing loops. We illustrate its effectiveness by generating efficient CUDA codes for four graph analytic algorithms, and comparing performance against their multicore OpenMP versions generated by Green-Marl. In particular, our generated CUDA code performs comparable to 4 to 64-threaded OpenMP versions for different algorithms.